2020
DOI: 10.1016/j.advwatres.2020.103658
|View full text |Cite
|
Sign up to set email alerts
|

Flow of shear-thinning fluids through porous media

Abstract: Porous media Homogeniz.adon Adjoint theory Carreau fluids Pseudo-plastic fluids exhibit a non-Jinear stress-strain relationship which can provoke large, localized viscosity gradients. For the fl ow of such fl uids in porous media the consequence is a strong varia b ility of the effective permeability with poroeity, angle of the macroscopic pressure gradien t, and meological parameters of the fluid. Such a variability is investigated on the basis of ad j oint homogenization theory for a Carreau fluid in an idea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 32 publications
2
22
0
Order By: Relevance
“…This observation is relevant because it allows for the closure problem defined in Eqs. (31) to reduce, under non-inertial and steady-state conditions, to the one reported in Section 3 in [38].…”
Section: Upscalingmentioning
confidence: 80%
See 2 more Smart Citations
“…This observation is relevant because it allows for the closure problem defined in Eqs. (31) to reduce, under non-inertial and steady-state conditions, to the one reported in Section 3 in [38].…”
Section: Upscalingmentioning
confidence: 80%
“…For example, the macroscopic flux to force relationship has been inferred from simplified representations of the porous structure under the form of bundles of capillaries [18,19] and pore-network models [20,21]. More formal approaches have also been employed, including the thermodynamically https://doi.org/10.1016/j.jnnfm.2022.104840 constrained averaging theory (TCAT) [22], the classical [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] and adjoint [38] homogenization techniques and the volume averaging method [39][40][41][42]. In the following paragraphs a brief literature review, mainly focused on applications of the homogenization and volume averaging methods, is presented.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 The same experiments have shown that the inertia coefficients ζ i also depend on viscosity; this appears reasonable for relatively small Reynolds number flows. 21 However, no theory exists, to deal with the rather complicated geometry of headers (and the complicated flow distribution therein), allowing the extrapolation of the results to liquids of different viscosities.…”
Section: Case II Iso Protocol 11mentioning
confidence: 99%
“…The two closure problems I and II are coupled both between themselves and also with the macroscale model solution due to the convective terms in Equations ( 29c) and (30c). This becomes clear when, in these two last equations, the representation given in Equation ( 28a) is used to expressṽ and v in terms of ∇ p β and f. This issue is often encountered while upscaling non-linear processes (see, for instance, Valdés-Parada et al, 2009;Airiau and Bottaro, 2020) and it will be addressed later in section 6.3. At this point, it is pertinent to derive the closed form of the upscaled model.…”
Section: Local Closure Problemmentioning
confidence: 99%